Islamic Republic of Afghanistan : Third Review Under the Staff-Monitored Program and Request for an Extension. (IMF Staff Country Reports; Country Report ;, 2005)
This paper assesses Afghanistan's Third Review Under the Staff-Monitored Program (SMP) and Request for an Extension. Performance during the third quarter of the SMP was strong, particularly considering that the October 2004 presidential elections and the ensuing formation of a new government diverted important human resources. All end-December 2004 indicative quantitative indicators and structural benchmarks were met, except for the benchmark related to the publication in the official gazette of the central bank law and the commercial banking law, as the publication of the latter was delayed for technical reasons.